Enhancing Antibacterial Performance: Structure, Phase Composition, and Microroughness of Selective Plated Copper Coatings on Medical-Grade Stainless Steel 1.4021 and Nickel Alloy Ni200 - Deyan Veselinov; Hristo Skulev; Radostina Yankova; Stoyan Ivanov; Thomas Fintan Moriarty; Boyko Gueorguiev (Applied Sciences, 2023)
This study presents a preliminary characterization of selective plated antibacterial copper coatings on medical-grade stainless steel 1.4021 and nickel alloy Ni200 substrates using two different copper electrolyte solutions with acidic and alkaline pH. The characterizations included analysis of the microstructure, phase composition, surface roughness, and antibacterial activity against Gram-positive Staphylococcus aureus ATCC 29213 and Gram-negative Escherichia coli ATCC 25922 bacteria. The results revealed uniform and continuous layers of single-phase solid-solution copper coatings without any cracks or defects. The coatings, produced using acidic or alkaline solutions, exhibited approximately 20% or 40% lower surface roughness compared to the substrate roughness. This suggests that the plating process led to a smoother surface finish. Importantly, all of the selective plated copper coatings exhibited antibacterial properties. Inhibition zones were identified, indicating the ability of the coatings to inhibit the growth of both Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria. The use of the alkaline copper solution resulted in slightly larger inhibition zones compared to the acidic solution, indicating enhanced antibacterial activity. These findings suggest that the selective plated copper coatings on medical-grade stainless steel 1.4021 and nickel alloy Ni200 substrates have the potential to be effective antibacterial surfaces.